Interactions among Polycomb Domains Are Guided by Chromosome Architecture - Tolhuis, Bas; Blom, Marleen; Kerkhoven, Ron M.; Pagie, Ludo; Teunissen, Hans; Nieuwland, Marja; Simonis, Marieke; de Laat, Wouter; van Lohuizen, Maarten; van Steensel, Bas (PLoS genetics, 2011)
Polycomb group (PcG) proteins bind and regulate hundreds of genes. Previous evidence has suggested that long-range chromatin interactions may contribute to the regulation of PcG target genes. Here, we adapted the Chromosome Conformation Capture on Chip (4C) assay to systematically map chromosomal interactions in Drosophila melanogaster larval brain tissue. Our results demonstrate that PcG target genes interact extensively with each other in nuclear space. These interactions are highly specific for PcG target genes, because non-target genes with either low or high expression show distinct interactions. Notably, interactions are mostly limited to genes on the same chromosome arm, and we demonstrate that a topological rather than a sequence-based mechanism is responsible for this constraint. Our results demonstrate that many interactions among PcG target genes exist and that these interactions are guided by overall chromosome architecture.